Localisation of C=C Bond and absolute quantification of unsaturated Fatty Acids in Vegetable Oils based on photochemical derivatisation reaction coupled with mass spectrometry. (20th February 2020) - Xu, Shuling; Wei, Fang; Xie, Ya; Wu, Bangfu; Lv, Xin; Qin, Zuojian; Chen, Hong
Summary: In this study, a strategy based on photochemical derivatisation and stable isotope labelling coupled with mass spectrometry (MS) for rapid and accurate identification and quantification of unsaturated fatty acids (UFAs) in vegetable oils was developed. Acetone was employed to label double bond(s) of UFAs via Paternò–Büchi (PB) reaction. The acetone‐labelled UFAs could produce diagnostic ions specific to the locations of carbon–carbon double bond (C=C) in collision‐induced dissociation (CID), which enabled confident assignment of C=C locations in UFAs. Furthermore, absolute quantification was achieved by using d6‐acetone‐labelled UFAs as internal standard to minimise the quantitation deviation due to nonuniformity response and ion suppression effects. By exploiting this method, precise identification and quantification of UFAs in nine kinds of vegetable oils including three kinds of Chinese special vegetable oils were achieved. This method exhibits a powerful potential use for the localisation of C=C bond(s) and quantitative analysis of UFAs, which is valuable for discovery of unusual UFAs in special oils and crops, and quality control of edible oils. Abstract : Unsaturated fatty acids (UFAs) from vegetable oils reacted with acetone via Paternò‐Büchi reaction. Fragment ions specific to the locations of carbon–carbon (C=C) bonds were generated from acetone labeled UFAs in collision‐induced dissociation (CID), which enabled confident assignment of C=C locations in UFAs. Meanwhile, stable isotope labeling strategy was employed for accurate quantification.